Critical perspective of English teaching and learning in Turkey - Omer Gokhan Ulum; Kutay Uzun (Institute of Advanced Engineering and Science, 2020)
GTM (Grammar Translation Method) is still the commonly utilized method in EFL classes in Turkish Education System. Based on a phenomenographic research design, this paper inquires the personal constructs of EFL state school teachers (n= 15) on the related issue. There in lies the major result in that non-native EFL teachers, who have learnt English totally via GTM, teaches it via GTM as well. Implications are provided to overcome this vicious circle.